Spatial Distribution of Caves and Cave Species in Nepal: A Review - Rai, Raju; Manchi, Shirish S.; Zhaofeng, Wang; Bhatta, Kabindra (Geographical Journal of Nepal, 2025)
A cave is a natural underground hollow with a dark passage accessible to humans, naturally made by rock erosion or melting ice over a long period. Caves have fascinated humans for centuries for their appearance and biological diversity. Caves have played essential roles in various cultures, mythology and history. Many caves in Nepal are cultural sites for many societies. They are also significant for habitats for various cave-dwelling vertebrate and non-vertebrate species. The country has several caves that are used for tourism activities. This study found 222 caves known from within 56 districts of Nepal. Surkhet, Mustang, and Salyan districts possess the highest number of caves, totaling 21, 15, and 12 caves, respectively. Spatially, caves are largely found in the country's Hill and Middle Mountain regions. The Hill region found the highest number of caves (n= 136). Similarly, 34, 26 and 1 caves are located in the Middle Mountain, Siwalik, High Mountain and Tarai regions,respectively. This study has analyzed the caves in various importance. About 36.7% of caves in Nepal have cultural and religious significance, about 17.7% are important for flora and about 15.5% are significant for wild species. We looked into the spatial distribution of caves based on various secondary sources mentioned in reports, research papers, books, and municipality profiles. Based on the existing literature, most of the caves are roosting sites for bats, and some caves are used as cultural sites and tourist sites. Caves and cave management for cultural, tourism, and fauna conservation have emerging challenges in Nepal due to a lack of proper management, which requires establishing cave policies and adequate planning for wild species.